GRACILIANO HERÓI: AS CONTINGÊNCIAS DO HUMANO EM CONTEXTO DE MATERIALIDADES HISTÓRICAS ADVERSAS - Cunha, João Manuel dos Santos (Organon, 2012)
By appropriating Graciliano Ramos’s text Memórias do cárcere (1953), film director Nelson Pereira dos Santos makes use of a filmic transcreation (1983) to contextualize and reconfigure (both socially and culturally) the status of the narrator as memoirist in literature. As he blurs any attempt at a clear-cut hierarchization of the textualities involved, the cinematographic author promotes the resonance of two different periods in 20th century Brazilian history: Vargas’s dictatorship (1930-1945), as lived by Graciliano Ramos himself, and that of the military régime post-1964. An interpretation of both works, considered here as being founded upon the transversal theme of the need to reformulate the past, a result of the condensation of historical time in the present which gives shape to both narratives, may be especially meaningful in the sense that it bears witness to art’s capability to shed light upon human contingence in historically dark times.